Family planning with inflammatory bowel disease: the challenge of childlessness and parent concerns - Walldorf, Jens; Pijan, Emilia; Greinert, Robin; Riesner-Wehner, Anica; Michl, Patrick (Zeitschrift für Gastroenterologie, 2021)
Background In patients with inflammatory bowel disease (IBD), diagnosis is often established at the beginning of childbearing age. Accordingly, concerns about family planning and pregnancy (FPP) are common. Poor knowledge regarding FPP might contribute to increased childlessness in patients with IBD.Methods The Crohn’s and Colitis Pregnancy Knowledge Score (CCPKnow, 17 multiple-choice questions) was translated into German and then used for a web-based survey. Childlessness was analyzed with respect to socio-demographic and disease-related information, and the knowledge (CCPKnow) and concerns of IBD patients with children were compared to those of voluntarily childless (VC) and non-voluntarily childless (NVC) IBD patients.Results Childlessness was observed in 57.4 % of the 533 participants (90.6 % women, 63.0 % Crohn’s disease, 31.5 % ulcerative colitis, mean age 33.2 ± 8.6 years), voluntary childlessness in 9 %. The mean overall CCPKnow was adequate (9.38 ± 3.96). Poor knowledge was not associated with increased childlessness (CCPKnow of < 8 was found in 29.8 % of patients with children and 28.9 % of childless patients, p > 0.5). Instead, the patients’ education, medical advice, FPP-related concerns, impaired body image, and sexual dysfunction had a significant impact on childlessness. Frequent concerns included adverse effects of the patient’s medication on their child (36 % of the respondents), malformation (33 %), miscarriage (34.5 %), and the inheritability of IBD (57 %).Conclusions Factual knowledge does not reduce disease-related concerns or childlessness. Correct but possibly bothersome information on FPP might contribute to childlessness in patients with IBD. Our findings underline the need for qualified counseling of IBD patients regarding FPP by an experienced IBD physician.
Keywords: inflammatory bowel disease; pregnancy; family planning; childlessness